Progress in the lattice simulations of Sp(2N) gauge theories - Biagio Lucini (Proceedings of Science, 2019)
We report on the status of our programme to simulate Sp(2N) gauge theories on the lattice. Motivated by the potential realization of an SU(4)/Sp(4)∼SO(6)/SO(5) composite Higgs model and the applications to self interacting dark matter, we first perform dynamical simulations of Sp(4) theories with two Dirac flavors in the fundamental representation. Preliminary results of the meson spectrum are presented, along with discussion of the lattice systematics. We also introduce two-index anti-symmetric Dirac fermions. Such fermions are relevant in the context of partial top compositeness scenario, provided they carry SU(3) color quantum numbers, and hence we introduce three (Dirac) copies of them. We present the quenched meson spectrum and explore the phase space of bare lattice parameters. For all the numerical simulations we use the standard Wilson lattice gauge and fermion actions.